2016
DOI: 10.1353/hpu.2016.0061
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Ho‘ouna Pono Curriculum: A Pilot Study of Culturally Grounded Substance Abuse Prevention for Rural Hawaiian Youth

Abstract: This pilot study evaluated the Hoʻouna Pono curriculum, which is a culturally grounded, school-based, drug prevention curriculum tailored to rural Native Hawaiian youth. The curriculum focuses on culturally relevant drug resistance skills training and is aligned with the State of Hawaiʻi academic standards. Six Hawaiʻi Island public middle/intermediate schools randomly assigned to intervention or treatment-as-usual comparison conditions (N = 213) were evaluated in this study. Paired sample t-tests separating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…An ongoing effort in Hawai'i with rural, Native Hawaiian communities seeks to identify risk, resilience, and cultural protective factors from substance use disorders among youth (Okamoto, Helm, Kulis, Delp, & Dinson, ) and develop and test a culturally grounded curriculum to prevent drug use and measures of its impacts (Helm & Okamoto, ; Okamoto, Kulis, Helm, Lauricella, & Valdez, ; Okamoto, Helm et al., ). The translational trajectory of this research team in many ways mirrors the People Awakening pathway in starting with exploratory studies to identify key risk and protective factors for drug use among youth and paying particular attention to factors specific to a Native Hawaiian cultural and community context.…”
Section: Development Of Relationship In Cbpr With Indigenous Communitiesmentioning
confidence: 99%
“…An ongoing effort in Hawai'i with rural, Native Hawaiian communities seeks to identify risk, resilience, and cultural protective factors from substance use disorders among youth (Okamoto, Helm, Kulis, Delp, & Dinson, ) and develop and test a culturally grounded curriculum to prevent drug use and measures of its impacts (Helm & Okamoto, ; Okamoto, Kulis, Helm, Lauricella, & Valdez, ; Okamoto, Helm et al., ). The translational trajectory of this research team in many ways mirrors the People Awakening pathway in starting with exploratory studies to identify key risk and protective factors for drug use among youth and paying particular attention to factors specific to a Native Hawaiian cultural and community context.…”
Section: Development Of Relationship In Cbpr With Indigenous Communitiesmentioning
confidence: 99%
“…This study expands upon Okamoto et al’s (2016) and Okamoto and Helm’s (2015) quantitative findings by qualitatively analyzing the influence of relational harmony on drug resistance strategies within Native Hawaiian families. In order to effectively deal with drug-related problem situations involving family members, Hawaiian youth need to be able to balance instrumental goals (i.e., drug refusal) with relational goals (i.e., maintaining family harmony).…”
Section: Literature Reviewmentioning
confidence: 69%
“…Recent pilot/feasibility drug prevention research focused on rural Hawaiian youth suggests that maintaining relational harmony among family members may play an important role in the types of strategies used within drug-related problem situations. Okamoto, Kulis, Helm, Lauricella, and Valdez (2016) evaluated the Ho‘ouna Pono curriculum, which is a school-based, drug prevention curriculum that includes videos depicting offers to use substances by peers and family members. The pilot evaluation of the curriculum had shown a significant effect on improving interpersonal relationships, demonstrated through ameliorating fighting behavior for youth exposed to the intervention at 6- and 12-month follow up (Okamoto et al, 2016; Okamoto & Helm, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple evaluations with different samples have shown promising findings for the Ho‘ouna Pono curriculum. For example, a pilot evaluation ( N = 213) across three waves of data (pretest data collection before administering the curriculum, posttest data collection immediately following the delivery of the final lesson, and 6‐month follow‐up) demonstrated positive findings related to assessment of situational risk, use of drug‐resistance strategies, and dealing with interpersonal conflict (Okamoto, Kulis, Helm, Lauricella, & Valdez, ). Compared with youth in the control schools, paired sample t tests of mean difference scores indicated that youth in the intervention schools thought significantly more about the consequences resulting from accepting drugs from pretest to 6‐month follow‐up.…”
Section: Literature Reviewmentioning
confidence: 99%